Assessment of the hematological profile and pathohistological changes in hepatic and renal tissue in adult rats exposed to different dietary components - Nadža Kapo-Dolan; Dina Kapić; Esad Ćosović; Elmir Čičkušić; Aida Bešić; Nedim Čović; Nedžad Hadžiomerović; Amir Zahirović; Muhamed Katica (Open Veterinary Journal)
Background: Different dietary components can potentially affect the hematological and biochemical profile, and cause pathohistological changes in liver and kidney tissue.